THE STRUCTURAL GEOLOGY STUDY AND SLOPE STABILITY ANALYSIS IN KARANGBAWANG VILLAGE, AJIBARANG, CENTRAL JAWA - Setiawan, Jatmika; Setiawan, M. Nurjati; Rahman, M. Gazali; Prasetyo, Abdullah Panji; Hapsari, Nuli (Universitas Pembangunan Nasional Veteran Yogayakarta, 2022)
Engineering geology or Geotechnical is the application of geological science in engineering practice for the purpose of ensuring that geological factors affecting the location, design, construction, operation and maintenance of engineering works have been properly identified and taken into account. Engineering geology research can be carried out during the planning, environmental impact analysis, civil engineering design, optimization engineering and construction stages of public and private projects, as well as in the post-construction and project investigation stages. Engineering geology research is carried out by a geologist or an educated engineering geologist, trained professionals and has the ability to recognize and analyze geological hazards and adverse geological conditions. The whole purpose is to protect life and property from damage as well as solutions to geological problems. Geological observations made in the form of geological structures in the form of joints and faults are very important parameters carried out in the planning stage of a development because it is very influential in the short, medium and long term stability of a civil building. Detailed measurements and mapping of the intensity level of geological structures will be able to assist engineering geologists in making recommendations for a civil construction project. Geological engineering study of the Ajibarang area and its surroundings, especially in the area of PT.development project crusher and conveyor. So that it will get good slope safety and can be used as the basis for the development of the crusher and conveyor at PT. Semen Bima.